FRAME ANALYSIS OF MICROTEACHING IN A COMMUNITY OF PRACTICE OF TEACHERS OF ENGLISH AS AN ADDITIONAL LANGUAGE IN SOUTHERN BRAZIL - Kirsch, William; Sarmento, Simone (BELT - Brazilian English Language Teaching Journal, 2021)
The purpose of this study is to discuss the discourse practice of microteaching in a teaching community consisting mainly of students pursuing the teacher certification in English as an Additional Language in southern Brazil. The study relies on qualitative methods of data generation and analysis as well as on the framework of interactional sociolinguistics. Results suggest microteaching is a highly complex practice, with a recurring pattern. Additionally, they suggest that students who are considered successful in a microteaching session are those who produce such pattern in their micro-classes. We conclude by suggesting that informing participants about the expectations regarding the structure of microteaching before they engage in it is desirable.